Trace element concentrations in fine sediment and linkages to non-point pollution source: Lower Johor river basin - L S Mazilamani; K V Annammala; Anand Nainar; M Z M Najib (IOP Publishing Ltd, 2020)
Johor Strait is an economically important freshwater system in the southern portion of Peninsular Malaysia. In past decades, Johor has been experiencing rapid developments especially in industrialisation, urbanisation and agricultural activities which have impacted the quality of Johor river. This study focused on identifying the intensity and degree of sediment contamination by trace elements from different anthropogenic sources using the multiple Risk Indexes. Inductively Coupled Plasma-Mass Spectrometry (ICP-MS) was used to detect trace element concentrations from nine sampling stations. The overall ranges for metals are 0.35- 4.25, 505.86-1864.56, below detection limit (BDL)-5.37, 0.02-0.07, 0.02-0.17, 0.59-2.05, BDL-5.35, 247.07-1010.23, 0.71-9.62, 1.08-5.68 and 10.87-21.15 mg/kg for Ag, Al, As, Cd, Co, Cr, Cu, Fe, Mn, Ni, and Zn respectively. The mean concentrations of trace elements follow the order: Al > Fe > Zn > Cu > Mn > Ni > Ag > Cr > As > Co > Cd. In this study, high concentrations of most elements (Al, As, Cd, Co, Fe, Mn, and Ni) were recorded at SS5 as the station is located near the Kota Tinggi city. Comparison with the sediment quality guidelines (SQGs) portrayed that concentrations of As, Cd, Cr, Cu, Ni, and Zn were below the Threshold Effects Level (TEL), Severity Effects Level (SEL), Probable Effects level (PEL) values in all sampling stations. The Pollution Load Index (PLI) that ranged between 0.151 and 0.389 (PL1 < 1) indicates that the Johor river sediments are free of trace element contamination. Potential Ecological Risk Index (RI), and Potential Ecological Risk Factor (Er) were in the range of 3.018-11.823 (RI < 150) and 0.103-7.141 (Er <40) respectively, which indicate that trace elements in Johor river pose no adverse effects on aquatic biota. The Pearson’s correlation matrix showed a good positive correlation between Al and As (0.546), Co (0.595), Fe (0.440), Mn (0.770), and Ni (0.496), representing similar sources of pollution. The cluster analysis indicates that Al, Mn, As, Ni, Fe, Cd, and Co originated from natural processes while Cr, C, Ag, and Zn are mainly from anthropogenic sources. Suggesting that man-made activities are accelerating sedimentation rate and washing down the pollutants together to the adjacent water bodies. Tracing the origin of the elements and planning for target mitigation to reduce further deterioration to the receiving river system could be the next mode of action.